Accelerated Development With Increased Bone Mass and Skeletal Response to Loading Suggest Receptor Activity Modifying Protein-3 as a Bone Anabolic Target - Pacharne, Suruchi; Livesey, Matthew; Kadmiel, Mahita; Wang, Ning; Caron, Kathleen M.; Richards, Gareth O.; Skerry, Tim M. (Frontiers in Endocrinology, 2022)
Knockout technologies provide insights into physiological roles of genes. Studies initiated into endocrinology of heteromeric G protein-coupled receptors included deletion of receptor activity modifying protein-3, an accessory protein that alters ligand selectivity of calcitonin and calcitonin-like receptors. Initially, deletion of RAMP3 appeared phenotypically silent, but it has emerged that mice have a high bone mass phenotype, and more subtle alterations to angiogenesis, amylin homeostasis, and a small proportion of the effects of adrenomedullin on cardiovascular and lymphatic systems. Here we explore in detail, effects of RAMP3 deletion on skeletal growth/development, bone mass and response of bone to mechanical loading mimicking exercise. Mouse pups lacking RAMP3 are healthy and viable, having an accelerated development of the skeleton as assessed by degree of mineralisation of specific bones, and by microCT measurements. Specifically, we observed that neonates and young mice have increased bone volume and mineralisation in hindlimbs and vertebrae and increased thickness of bone trabeculae. These changes are associated with increased osteoblast numbers and bone apposition rate in RAMP3-/- mice, and increased cell proliferation in epiphyseal growth plates. Effects persist for some weeks after birth, but differences in gross bone mass between RAMP3 and WT mice lose significance in older animals although architectural differences persist. Responses of bones of 17 week old mice to mechanical loading that mimics effects of vigorous exercise is increased significantly in RAMP3-/- mice by 30% compared with WT control mice. Studies on cultured osteoblasts from RAMP3-/- mice indicate interactions between mRNA expression of RAMPs1 and 3, but not RAMP2&3. RAMP3-/- osteoblasts had increased expression β-catenin, a component of the canonical Wnt signalling pathway known to regulate skeletal homeostasis and mechanosensitivity. Given interactions of RAMPs with both calcitonin and calcitonin-like receptors to alter ligand selectivity, and with other GPCRs to change trafficking or ligand bias, it is not clear whether the bone phenotype of RAMP3-/- mice is due to alterations in signalling mediated by one or more GPCRS. However, as antagonists of RAMP-interacting receptors are growing in availability, there appears the likelihood that manipulation of the RAMP3 signalling system could provide anabolic effects therapeutically.